Experimental investigation of mechanical properties for wrought and selective laser melting additively manufactured SS316L and MS300. (2022) - Gor, Meet; Soni, Harsh; Singh Rajput, Gautam; Sahlot, Pankaj
Abstract: Additive manufacturing (AM) is a disruptive technology used in many industries due to the superior mechanical, surface and microstructural properties. Selective laser melting (SLM) is one of the metal additive manufacturing techniques used to fabricate complex metallic components. SLM involves a laser as a heat source and powder as a raw material to build a three-dimensional geometry with layer-by-layer material deposition. The layer-by-layer manufacturing induces very different microstructure evolution than conventional manufacturing processes and results in different mechanical properties. There is a need to compare the different mechanical properties of SLM additively manufactured (SLM-AM) with the wrought materials. In this study, the mechanical properties of both SS316L stainless steel and MS300 maraging steel produced by selective laser melting are examined and compared with the conventional manufacturing processes. Mechanical properties such as tensile strength, hardness and density are compared for SLM-AM and wrought samples. Additively manufactured SS316L and MS300 shows good tensile strength and hardness. The tensile strength of 640 MPa for SS316L and 1057 MPa for MS 300 materials was observed for SLM-AM build samples, approximately 5 to 10 % higher than wrought materials. The hardness value of 258 HV and 397 HV is obtained for AM build samples of SS316L and MS300 respectively, which is higher than wrought materials. The hardness value has been observed 17% higher for SLM SS316L and 13% higher for MS300 material compared to wrought. However, elongation is observed higher in wrought samples compared to SLM build samples. This study highlights the advantages of additively manufactured SS316L and MS300 in comparison with wrought alloys.